Association of depression with dental caries and periodontal disease at a tertiary care hospital - Owais Kareem; Bushra Ijaz; Shaheen Anjum; Sadia Hadayat; Iqra Tariq; Maria Younis (Journal of the Pakistan Medical Association, 2021)
Published in May - 2021